2008
DOI: 10.1364/oe.16.015382
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic polaritons in Fibonacci quasicrystals

Abstract: The fabrication and characterization of light-emitting one-dimensional photonic quasicrystals based on excitonic resonances is reported. The structures consist of high-quality GaAs/AlGaAs quantum wells grown by molecular-beam epitaxy with wavelength-scale spacings satisfying a Fibonacci sequence. The polaritonic (resonant light-matter coupling) effects and light emission originate from the quantum well excitonic resonances. Measured reflectivity spectra as a function of detuning between emission and Bragg wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In the limit of infinite systems, the transmission bands form a Cantor set with Lebesgue measure zero, and it is assumed that either only complete transmission or complete reflectance occurs [9,10]. However, for physical applications usually systems with relatively small numbers of layers are used [4,6]. In Figure 3, the results for the transmission coefficients T(#, !)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the limit of infinite systems, the transmission bands form a Cantor set with Lebesgue measure zero, and it is assumed that either only complete transmission or complete reflectance occurs [9,10]. However, for physical applications usually systems with relatively small numbers of layers are used [4,6]. In Figure 3, the results for the transmission coefficients T(#, !)…”
Section: Resultsmentioning
confidence: 99%
“…In this context, quasicrystals, which are regarded as having a degree of order intermediate between crystals and disordered systems, are of special interest because they often possess unexpected physical properties due to their complex symmetries [1][2][3]. This qualifies them for the potential application in several optical devices such as single-mode light-emitting diodes, polarization switches, and optical filters [4][5][6]. An interesting application is also the construction of microelectronic devices that are based on photons rather than on electrons, so that they potentially can be the electromagnetic analogue of semiconductors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] More recently, researchers have tried to apply intriguing physical properties of these structures to designing efficient nanophotonic devices. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Quasiperiodic systems possess properties which are intermediate between those of periodic systems and random systems. As is well-known, band gaps appear in the density of states of periodic systems and affect many of their physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the optical properties of quasi-periodic QWs have been investigated and have been compared with those of periodic ones [22][23][24][25]. In particular, in terms of light emission, the results have shown that the PL intensity in a Fibonacci quantum well (FQW) is significantly stronger than that in a PQW, not only under the Bragg condition, but also under the anti-Bragg condition [23,26]. It has also been found that the properties of PL intensity in a Thue-Morse quantum well (TMQW) are similar to those in a PQW [5].…”
mentioning
confidence: 99%
“…5(d). This can be attributed to the enhanced lightmatter coupling because of the larger field at the QWs in the DPQWs [5,23,26].…”
mentioning
confidence: 99%